Inconspicuous coarticulation: A complex path to sound change in the tone system of Hanoi Vietnamese. (November 2016) - Brunelle, Marc; Hạ, Kiều Phương; Grice, Martine
Abstract: In Hanoi Vietnamese, the rising and falling tones are frequently confused before the (high) level tone, even though they are clearly distinct in other contexts. In this paper, we conduct production and perception experiments designed to assess the source of this confusion. We argue that the peak of the rising tone is normally delayed onto the initial portion of the following tone, but that this peak delay lacks acoustic and perceptual salience when this following tone is a level tone. As a result, the rising tone before a level tone is often perceived as a falling tone. Although we rule out the possibility that the tonal pattern under investigation is a phonological alternation, we propose that the complex coarticulatory and perceptual mechanisms that underlie it could account for the development of other instances of regressive tone sandhi. Highlights: The lack of salience of coarticulatory cues can cause perceptual confusion. The peak of the Hanoi Vietnamese rising tone is delayed onto the following syllable. As the delayed peak is not salient on a high level tone, two tones are confused. This perceptual confusion could explain the development of regressive tone sandhi.